Professionalism values of Generation Z nursing students - Pramesti Arnetha Indriyanti; Dodi Wijaya; Kholid Rosyidi Muhammad Nur (KHD-Production, 2025)
During nursing education, professional values are developed in theoretical and clinical education. Nursing students are expected to cultivate professional values when they enter university and continue their nursing practice. This study aims to analyze the professionalism values of Generation Z nursing students. The research employed a descriptive design, including 182 respondents selected through total sampling. Data were collected using a questionnaire. The research instrument used the Nurse Professional Values Scale-Revised (NPVS-R) questionnaire. Data analysis used descriptive analysis with data not normally distributed (median). The average age of the students was 21, with a majority being female. The indicators of professional values nursing students’ altruism, autonomy, human dignity, integrity, and social justice have median values of 31, 30, 50, 46, and 27. The results showed that nursing students who had good and less professional values were in the same amount. This shows that Generation Z nursing students have a different understanding of the current values of professionalism. The results of this study are expected to be a reference in improving the ability of professionalism values in Generation Z nursing students.